Pengembangan E-LKPD Berbasis Project Based Learning Pada Mata Pelajaran IPAS Kelas V - Nurul Kamila; Lidia Simanihuruk; Lala Jelita Ananda; Fajar Sidik Siregar; Suyit Ratno (Jurnal Keluarga Sehat Sejahtera, 2026)
Science and Social Studies learning in elementary schools still relies heavily on textbooks and printed worksheets, resulting in students who tend to be less active and less motivated in the learning process. This study aims to develop an Electronic Student Worksheet (E-LKPD) based on Project Based Learning (PjBL) on the topic of magnetic force in IPAS subject for fifth-grade students, and to examine its validity, practicality, and effectiveness as a learning medium. This study employed a Research and Development (R&D) approach using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 20 fifth-grade students at UPT SDN 064994 Medan. Data collection instruments included expert validation questionnaires, teacher and student response questionnaires, and multiple-choice tests in the form of pretest and posttest. Data were analyzed using validity and practicality percentage formulas, as well as the N-Gain formula to measure effectiveness. The results showed that the developed E-LKPD achieved an average expert validation percentage of 93% in the very valid category, an average practicality score of 92.3% from teachers and students in the very practical category, and an N-Gain value of 0.66 in the medium category, which is declared effective. Therefore, the PjBL-based E-LKPD developed is suitable for use as an interactive and contextual IPAS learning medium in fifth-grade elementary school.